The innovators [compact disc, unabridged] : how a group of inventors, hackers, geniuses, and geeks created the digital revolution - Isaacson, Walter (Simon & Schuster Audio, 2014)
The computer and the Internet are among the most important inventions of our era, but few people know who created them. Most innovations of the digital age were made collaboratively. There were a lot of fascinating people involved, some ingenious and a few even geniuses. This is the story of these pioneers, hackers, and entrepreneurs, how their minds worked and what made them so creative. It's also a narrative of how their ability to work as teams made them even more creative.